2018
DOI: 10.1159/000494358
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hospitalization After Ureteroscopy Plus Elective Double-J Stent as an Outpatient Procedure

Abstract: Purpose: To evaluate the safety and feasibility of ureteroscopy plus elective double-J stent as an outpatient procedure in an unselected population with regard to the treatment for ureteral calculi and to present a multivariate analysis of factors predict hospitalization. Materials and Methods: Ureteroscopy was performed as an outpatient procedure on 308 consecutive patients with ureteral stones. Contraindication for day case surgery was the only exclusion criteria from the study. All causes that led to immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…In a retrospective analysis of 2,010 ureteroscopies, researchers found out that operation time was signi cantly higher in patients with complications compared to patients without complications [19]. Salciccia and colleagues showed that longer operation time is strongly associated with hospitalization need after ureteroscopy [20]. Additionally, longer operation times was found to be associated with higher grade complications (Clavien score ≥ III) such as ureteral perforation, infectious complications and urosepsis after ureteroscopy [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of 2,010 ureteroscopies, researchers found out that operation time was signi cantly higher in patients with complications compared to patients without complications [19]. Salciccia and colleagues showed that longer operation time is strongly associated with hospitalization need after ureteroscopy [20]. Additionally, longer operation times was found to be associated with higher grade complications (Clavien score ≥ III) such as ureteral perforation, infectious complications and urosepsis after ureteroscopy [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the antimicrobial capabilities of EEP coating, its long‐lasting antimicrobial performance is another concern that needs to be considered, especially for patients who require long‐term indwelling ureteric stents. Ureteric stent removal is recommended 2–8 weeks after ureteric lithotripsy [32] or even longer in severe cases [33]. Thus, an antimicrobial duration of 8 weeks (2 months) or more is preferable.…”
Section: Methodsmentioning
confidence: 99%
“…There also has been an attempt to predict the stone-free rate (SFR) prior to RIRS with the R.I.R.S scoring system and a statistical approach [ 13 ]. In terms of statistical approach, [ 14 ] investigated the ureteroscopy plus elective double-J stent treatment using a multivariate analysis of factors predict hospitalization. The referenced study investigators assumed that all the procedures were routinely conducted and would only predict outcomes from the procedures.…”
Section: Introductionmentioning
confidence: 99%